Прогнозування поведінки споживачів на підставі теорії поширення інновацій: теоретичні засади і можливості практичного застосування - Соколовський, І. (Социология: теория, методы, маркетинг, 2009)
Forecasting plays important role in marketing activity of company. The FutureView™ is one of the methods developed by TNS Company and based on Diffusion of Innovations Theory. Traditional Early Adopters definition proposed by Rogers was revised and modified; therewith main principles of adaptation theory were maintain ed. Additional dimension of consumers, which allows identifying if they have power and potential to impact on future consumption process was added. Survey of potential users of investment funds for natural persons, conducted by TNS in Ukraine, is shown as an example of this solution applying. By way of example, the author shows the application of the FutureView™ that gives possibility to receive more complete and deep understanding of the future consumers’ behavior regarding new products and services, these consumers’ needs, motivations, social and demographic characteristics.